Head of Regional Role In Making Good Governance - Samran H Simbolon (International Journal on Social Science, Economics and Art, 2021)
This study tried to describe and analyze the role of local leaders in charge of a region to achieve a good and clean government. This study specifically analyzed the role of JR Saragih as Regent Simalungun in achieving good governance in Simalungun. This study uses the concept of good governance and decentralization, tori role as a basis for analyzing problems that occur. In this study explained a few things related Simalungun and Regent JR Saragih. The results of the analysis in this study found three main points of how the regional administration of the appropriate concept of good governance implemented in Simalungun, government transparency, accountability and public participation Kabupten Simalungun. The conclusion of the study is Simalungun District Government led by JR Saragih have applied some of the principles of good government and trying to organize the best possible government.